2016
DOI: 10.1016/j.ceramint.2016.09.102
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of glass–ceramics prepared from high-carbon ferrochromium slag

Abstract: Glass-ceramics were successfully prepared from high-carbon ferrochromium slag (HCFS), and the optimum heat-treatment conditions were determined by analysis of the crystallization kinetics. The parent glass is first prepared in five different ratios of HCFS to waste glass (R(H/W)), then heat-treated separately at five heating rates (α) and monitored by DSC. As the value of R(H/W) increases from 0.60 to 1.67, the crystallization activation energy (E c) decreases from 253.41 to 183.52 kJ/mol. The nucleation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…These curves comply with the principle of non‐isothermal process, that is, the temperature of the maximum of the exothermic peak increases with the increase of the heating rate, which allows the study of the kinetic mechanism by DTA. Thus, T p increases from 827°C to 877°C when the heating rate increases from 10°C min −1 to 50°C min −1 ; this result is in good agreement with that reported in other studies 21,46,47 . According to Bai et al., 46 the increase in temperature with heating rate is related to the fact that heat transfer becomes more difficult as the heating rate increases.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These curves comply with the principle of non‐isothermal process, that is, the temperature of the maximum of the exothermic peak increases with the increase of the heating rate, which allows the study of the kinetic mechanism by DTA. Thus, T p increases from 827°C to 877°C when the heating rate increases from 10°C min −1 to 50°C min −1 ; this result is in good agreement with that reported in other studies 21,46,47 . According to Bai et al., 46 the increase in temperature with heating rate is related to the fact that heat transfer becomes more difficult as the heating rate increases.…”
Section: Resultssupporting
confidence: 91%
“…These curves comply with the principle of non-isothermal process, that is, the temperature of the maximum of the exothermic peak increases with the increase of the heating rate, which allows the study C min −1 ; this result is in good agreement with that reported in other studies. 21,46,47 According to Bai et al, 46 the increase in temperature with heating rate is related to the fact that heat transfer becomes more difficult as the heating rate increases. Accordingly, much more energy will be required for nucleation and crystallization processes to occur.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, glass-ceramics possess strong mechanical strength, excellent thermochemical stability, and outstanding corrosion resistance . Waste-derived glass-ceramics (WDGC) are generally prepared via a two-step process involving (i) vitrification of solid residues to homogeneous amorphous slags by melting (>1400 °C) and quenching, and (ii) controlled crystallization of the amorphous slags to compact and environmentally stable glass-ceramics by sintering (800–1100 °C). However, the main drawback of this method is the high treatment cost caused by high melting temperatures. Bingham et al demonstrated that vitrification of toxic wastes was not economically feasible on any substantial scale.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Research works that focused on the optimum heat treatment schedule, nucleation agent, and physical properties of glass ceramics have revealed some critical information about slag glass ceramics, and provided theoretical instruction for future studies on BF slag glass ceramics. [14][15][16][17] However, the industrial manufacture of glass ceramics related to molten blast furnace slag is confronted with many problems, and one of the most important reasons is that the understanding and control of structure and properties of melts are not thoroughly studied. For glass ceramics from BF slag, preparation of glass melt prior to heat treatment is always one of the most critical and necessary procedures.…”
Section: Introductionmentioning
confidence: 99%